Investigating the role of Process Drama in reducing Foreign Language Anxiety and improving the communicative ability of a group of adolescent Greek EFL students - Zachariou, Eirini (Trinity College (Dublin, Ireland). School of Education, 2023)
Having observed speaking anxiety in my students ever since I was a young English language teacher induced me to research its causes and find ways to diminish it. Process Drama is a humanistic teaching approach that promises to create affective space. To explore its effectiveness in alleviating the symptoms of foreign language speaking anxiety and improving the communicative skills in a group of adolescent EFL learners in Greece, I compared it to another approach widely used in schools worldwide, namely Communicative Language Teaching, which promises to improve positive affect. I conducted a convergent mixed methods research project combining quantitative and qualitative data. The students were invited to participate in eight workshops divided into two cycles. The Communicative Language Approach was used in the first cycle, and in the second, the children were introduced to Process Drama. Their opinions were collected through questionnaires, voluntary comments and interviews. Two critical friends invited observed them and evaluated their speaking ability and non- verbal cues. The main findings show that although both instructional approaches had anxiety- reducing effects, Process Drama reduced Foreign Language Anxiety the most in the majority of the participants. The children praised Process Drama for being stress-free, fun, creative and educational. They also emphasised that they were provided with a powerful sense of freedom.
Keywords: Drama in Education; Education